Análisis de la carga interna durante una temporada de balonmano femenino adolescente - Camacho-Cardenosa, M.; Camacho-Cardenosa, A.; Martinez Guardado, I.; Timon Andrada, R.; Olcina Camacho, G.; Brazo Sayavera, J. (Revista Ciencia del Deporte, 2017)
This study examined the internal load based on heart rate (HR) in a teenage female handball team, which is playing in a regional league, comparing these parameters between the first and second half of the matches. A total of 10 adolescent female handball players participated in the study (age 14.70 ± 0.67 years (range, 14-15), weight 55.78 ± 6.80 kg (range, 46.70-68.90), height 160.44 ± 8.53 cm (range, 150.00-177.00), BMI 21.60 ± 1.10 kg/m2 (range, 19.90-23.10), fat mass 30.89 ± 3.70 % Fat Mass (range, 24.40-35.60) and VO2max 35.00 ± 1.00 ml·min·kg-1 (range, 33.76-36.00). Heart Rate (n=120) analyses were registered throughout 12 official matches using Heart Rate monitors. Individual demands were categorized into six intensity zones based on % Maximum Heart Rate (HRmax): zone I: 0-50%; zone II: 51-60%; zone III: 61-70%; zone IV: 71-80%, zone V: 81-90 and zone VI: 91-100% of HRmax. Effective maximum and mean Heart Rate in the total match were 204.14?6.12 and 185.71?8.33 b·min-1, respectively. During the second half, effective maximum (201.71?5.23 vs 204.15?6.57 b·min-1; p=0.001) and effective mean (183.51?8.61 vs 189.67?7.47 b·min-1; p=0.000). Heart Rate decreased comparing to the first half. Female adolescent team handball players develop a high intensity during official matches. This intensity is higher in first half compared to the second half.